2016
DOI: 10.3130/jaabe.15.271
|View full text |Cite
|
Sign up to set email alerts
|

Using the Kano Model to Analyze the Formation of Regional Attractive Factors of Art Street in Taichung, Taiwan

Abstract: This research integrated the needs to the regional environments, residents, and tourists to discuss the attractive factors of regional characteristics of the public and private realm. Using Tunghai Art Street as an example, the criteria for regional activation were proposed to shape the tourist attraction with cultural and art characteristics. The preliminary investigation recorded the art installations in Art Street's pedestrian-only space and Corbusier Square, and observed the tourist behavior and activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Yang, Yan, and Ma () identified the preconditions for acquiring an electric vehicle, where the availability of charging stations is the must‐be attribute among others. Meanwhile, Chen, Ko, and Lee (), Högström, Rosner, and Gustafsson (), Lin, Fu, and Li (), Zhang and Wang (), and Chen and Ko () applied the Kano model to identify the indicators for the quality of environmental services in recreation areas such as a river bank, a snow park, a suburban mountain, an urban park, and a pedestrian street, respectively. Authors showed the aspects that should be considered in shaping an urban area and its attractiveness to locals and tourists.…”
Section: The Kano Model In Assessing Environmental Quality: Evidence mentioning
confidence: 99%
“…Yang, Yan, and Ma () identified the preconditions for acquiring an electric vehicle, where the availability of charging stations is the must‐be attribute among others. Meanwhile, Chen, Ko, and Lee (), Högström, Rosner, and Gustafsson (), Lin, Fu, and Li (), Zhang and Wang (), and Chen and Ko () applied the Kano model to identify the indicators for the quality of environmental services in recreation areas such as a river bank, a snow park, a suburban mountain, an urban park, and a pedestrian street, respectively. Authors showed the aspects that should be considered in shaping an urban area and its attractiveness to locals and tourists.…”
Section: The Kano Model In Assessing Environmental Quality: Evidence mentioning
confidence: 99%
“…We hypothesize that even though preference for fashion attributes can be different for varied customer groups, Kano’s theory should be able to classify those qualities. Existing literature suggest that Kano’s theory was confirmed in the research relevant to customer satisfaction (Rotar and Kozar, 2017), class room management (Bawa, 2017), online shopping features (Behdioglu and Cilesiz, 2016), attractiveness of art street (Chen and Ko, 2016), student-defined quality (Taifa and Desai, 2016) and vacation planning decision (Gregory, 2011). However, there are very few studies (see e.g.…”
Section: Introduction and Rationale For The Studymentioning
confidence: 96%
“…KTFT posits that tourist satisfaction is not based just on meeting the basic performance needs with tourist products (Chen & Ko, 2016;Lee, 2015). It is critical to also establish which attributes lead to increased satisfaction, which attributes simply meet a fundamental requirement minimizing dissatisfaction and lastly which attributes add to both satisfaction and dissatisfaction (Matzler & Sauerwein, 2002).…”
Section: Kano's Three-factor Theory (Ktft)mentioning
confidence: 99%